Consistency of My Bisexual Self. Issue 2 (2nd April 2016) - Twist, Markie L. C.
Abstract: This brief narrative account focuses on the meaning of 'bisexuality, ' and the individual bisexual identity development of the author. In the sharing of this journey another voice and related narrative is added to not only the larger bisexual communities, but also potentially to the larger dominant societal context as a whole. In addition, an opportunity to decrease bisexual invisibility and increase bisexual visibility is attained through the telling of stories such as the one presented. The author concludes with an invitation to empower and support fellow bisexual-identifying persons.